Peru—Additional Duty on Imports of Certain Agricultural Products (Complainant: Guatemala). (2018) - Unknown
Abstract : Economics, trade and finance — World Trade Organization — General Agreement on Tariffs and Trade — Agreement on Agriculture — Tariffs — Bilateral free trade agreements — Whether parties to WTO and GATT may modify their obligations by bilateral agreement — Dispute settlement mechanism Treaties — Interpretation — WTO agreements — Free Trade Agreements — Vienna Convention on the Law of Treaties, 1969, Article 31 — Whether declaratory of customary international law — Context — Common intention of Parties — Subsequent agreement under Article 31(3)(a) of Vienna Convention — Relevant rules of international law applicable in relations between Parties under Article 31(3)(c) Treaties — Application — Good faith — Entry into force — Vienna Convention on the Law of Treaties, 1969, Article 18 — Object and purpose — Dispute Settlement Understanding, 1994, Articles 3.7 and 3.10 — Waiver of right to challenge measure before WTO dispute settlement proceedings — Whether waiver explicit — Institution of proceedings — Abuse of right Treaties — Interpretation — WTO agreements — Free Trade Agreements — Dispute Settlement Understanding, 1994, Article 3.2 — Vienna Convention on the Law of Treaties, 1969, Article 31 — International Law Commission Articles on the Responsibility of States for Internationally Wrongful Acts, 2001 — Article 20 — Consent — Article 45 — Invocation of responsibility — Whether interpretation or modification Sources of international law — WTO agreements — Other international rules — Vienna Convention on the Law of Treaties, 1969 — Free Trade Agreements — Modification of WTO rights and obligations — Applicable law — Vienna Convention, Article 41 — Marrakesh Agreement Establishing the WTO, 1994, Article X — GATT 1994, Article XXIV — GATS, 1995, Article V — 1979 Enabling Clause — Lex specialis